Investigating Remote-Sensing Techniques to Reveal Stealth Coronal Mass Ejections - Palmerio, Erika; Nitta, Nariaki V.; Mulligan, Tamitha; Mierla, Marilena; O’Kane, Jennifer; Richardson, Ian G.; Sinha, Suvadip; Srivastava, Nandita; Yardley, Stephanie L.; Zhukov, Andrei N. (Frontiers in Astronomy and Space Sciences, 2021)
Eruptions of coronal mass ejections (CMEs) from the Sun are usually associated with a number of signatures that can be identified in solar disc imagery. However, there are cases in which a CME that is well observed in coronagraph data is missing a clear low-coronal counterpart. These events have received attention during recent years, mainly as a result of the increased availability of multi-point observations, and are now known as 'stealth CMEs'. In this work, we analyse examples of stealth CMEs featuring various levels of ambiguity. All the selected case studies produced a large-scale CME detected by coronagraphs and were observed from at least one secondary viewpoint, enabling a priori knowledge of their approximate source region. To each event, we apply several image processing and geometric techniques with the aim to evaluate whether such methods can provide additional information compared to the study of "normal" intensity images. We are able to identify at least weak eruptive signatures for all events upon careful investigation of remote-sensing data, noting that differently processed images may be needed to properly interpret and analyse elusive observations. We also find that the effectiveness of geometric techniques strongly depends on the CME propagation direction with respect to the observers and the relative spacecraft separation. Being able to observe and therefore forecast stealth CMEs is of great importance in the context of space weather, since such events are occasionally the solar counterparts of so-called 'problem geomagnetic storms'.